THE RECRUITMENT PROCESS OF THE HEAD OF LOCAL GOVERNMENT BY POLITICAL PARTIES IN MALANG RAYA REGION - Budhy Prianto; Dwi Suharnoko; Mardiyono (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2018)
Direct regional head elections are in the process of recruiting leaders in regions that can guarantee the representation of local people through a democratic process. In this process, theoretically and constitutionally political parties have important and strategic roles and functions. Unfortunately, the oligarchic practice that engulfed almost all political parties has internally and externally recognized the basic principles of democracy in the process of recruiting prospective leaders in the region. The democratic process is only procedural, not substantial. So far it is strongly suspected that the process of regional head elections is more colored by transactional politics. This paper aims first, to obtain an overview of the recruitment process of candidates by political parties in the regional head elections in the Malang Raya region. Second, to obtain a description that is the power of money not only in choosing candidates for the regional head, but also able to lull constituents and voters in determining the choice of regional heads. Third, to obtain an explanation of the impact of the transactional political process and the use of the power of money as well as the impact on the relationship between political parties and their constituents in the Malang Raya region.